The Microstructure of Amorphous Iron Nanoparticle - Lan, Mai Thi; Hong, Nguyen Van; Nhan, Nguyen Thu; Hung, Pham Khac (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract: We have investigated the microstructure of amorphous iron nanoparticle (NP) and its bulk counterpart using molecular dynamic simulation with an embedded atom method (EAM). The NP models have a spherical shape and surface thickness of 3.6 ± 0.125 Å. The microstructure of NP surface and core is analyzed through the coordination number distribution, density profile and distribution of simplex radius. Furthermore, the surface roughness has been identified via the distribution of distance from surface atom to NP surface. It was found that the microstructure of NP core is quite different from that of NP surface. However, their microstructure is almost independent on NP size. The simulation result shows that the NP as well as bulk counterpart contain a large number of "native vacancy". The glass transition temperature increases with NP size and depends on the fraction of surface atoms.           Keywords: structure, amorphous, nanoparticle, simulation, iron.